Transition Readiness Among Pre-licensure Nursing Students Entering Clinical Practice: A Systematic Review - Sujarwanto; Dodi Wijaya; Anisah Ardiana (Al-Hijrah Indonesia, 2026)
The theory-practice gap frequently triggers transition shock among pre-licensure nursing students. This study aims to identify, evaluate, and synthesize recent literature regarding the readiness level of professional nursing students transitioning to clinical practice. This systematic review adhered to the PRISMA protocol and searched PubMed, ScienceDirect, and Google Scholar for studies published over the last five years. Selection followed the PICOS framework, and methodological quality was appraised using the Joanna Briggs Institute (JBI) Checklist. Twelve articles from eight countries were analyzed. Quantitative findings indicate that practice readiness levels range from moderate to high, with mean scores averaging 63.5% to 75.4% of maximum capacity. However, significant variations exist, heavily influenced by healthcare contexts and educational cultures. Results confirm that readiness is multidimensional, integrating clinical skills, intrapersonal factors, teamwork, and professionalism. Limitations include a reliance on self-reported measures and the absence of a singular standardized assessment tool. Ultimately, these findings can directly inform nursing curriculum redesigns and the establishment of robust hospital-university partnership models, highlighting the critical need for structured pre-clinical orientations and integrated nurse residency programs to mitigate transition shock.